The challenges of capitalism for virtue ethics and the common good: interdisciplinary perspectives - Akrivou, Kleio; Sison, Alejo G. (Edward Elgar Publishing, 2016)
The evolution of modern capitalist society is increasingly being marked by an undeniable and consistent tension between pure economic and ethical ways of valuing and acting. This book is a collaborative and cross-disciplinary contribution that challenges the assumptions of capitalist business and society. It ultimately reflects on how to restore benevolence, collaboration, wisdom and various forms of virtuous deliberation amongst all those who take part in the common good, drawing inspiration from European history and continental philosophical traditions on virtue. -- Back cover